KOMBINASI PEMBERIAN PUPUK ANORGANIK GANDASIL D DAN NPK MUTIARA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERUNG (Solanum melongena L. Var. F1 Mustang) - Ratu Kamila Zahra Ghassani; Kiki Roidelindho; Dewi Firnia; Andi Apriany Fatmawaty (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2026)
Eggplant is one of the vegetable commodities favored by the community due to its nutritional content, such as vitamin C, vitamin B6, and potassium. However, eggplant production in Indonesia over the last three years has fluctuated due to unfavorable climatic conditions, as well as pest and plant disease attacks, which have contributed to decreased production. These problems can be addressed through the application of inorganic fertilizers, namely Gandasil D and NPK Mutiara, which contain balanced nutrients to support plant growth and increase yield. The objective of this study was to determine the effect of inorganic fertilizer application of NPK Mutiara and Gandasil D on the growth and yield of eggplant (Solanum melongena L.) Mustang F1 variety. This research was conducted in a screen house using a Randomized Complete Block Design (RCBD) with two factors and three replications. The first factor was the dosage of Gandasil D fertilizer (G0 = 0 g L⁻¹, G1 = 2 g L⁻¹, and G2 = 3 g L⁻¹), while the second factor was the dosage of NPK Mutiara fertilizer (N1 = 0 g plant⁻¹, N2 = 10 g plant⁻¹, N3 = 20 g plant⁻¹, and N4 = 30 g plant⁻¹). The observed parameters included plant height, number of leaves, number of fruits per plant, fruit length, fruit diameter, fruit weight, and shoot–root ratio. Data were analyzed using analysis of variance (ANOVA), and when significant effects were detected, further analysis was performed using Duncan’s Multiple Range Test (DMRT) at a 5% significance level to determine differences among treatments. The results showed that the application of Gandasil D fertilizer had a significant effect on plant height and number of leaves. In addition, NPK Mutiara fertilizer significantly affected plant height, number of leaves, number of fruits per plant, and fruit weight. The interaction between the two fertilizers significantly influenced plant height and number of leaves.